2002
DOI: 10.1007/s00221-001-0922-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuregulin and ErbB3 and ErbB4 after a traumatic lesion in the ventral funiculus of the spinal cord and in the intact primary olfactory system

Abstract: Neuron-derived neuregulins have been implicated in the regulation of glial cell function and survival. This factor family and its receptors may therefore be assumed to be of importance for the cellular response to traumatic injury. In this study we have examined the distribution of mRNA for neuregulin 1 (NRG1), ErbB3 and ErbB4-receptor tyrosine kinases after a ventral funiculus lesion in the lumbar spinal cord (VFL). The techniques used were in situ hybridization and immunohistochemistry. The survival times we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Thus, the loss of inputs combined with the close-to-cell-body section of the motor axon triggers degenerative events. Herein, VFC caused death of 67% of the motoneurons, which is in line with previous works [ 4 , 6 , 7 , 32 ]. After ventral root avulsion, in which the motor axons are pulled from the surface of the spinal cord, approximately 80% of motor neurons die within 2 weeks after lesion [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the loss of inputs combined with the close-to-cell-body section of the motor axon triggers degenerative events. Herein, VFC caused death of 67% of the motoneurons, which is in line with previous works [ 4 , 6 , 7 , 32 ]. After ventral root avulsion, in which the motor axons are pulled from the surface of the spinal cord, approximately 80% of motor neurons die within 2 weeks after lesion [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…The upregulation of NRG-1 and erbB receptors in the lesion area after injury may also account for the relatively lower concentrations of NRG-1 required in the in vivo studies compared with the amount required to block proliferation in the VSMC cultures. Similarly, the upregulation of NRG-1 and its erbB receptors has also been reported after ischemia and central nervous system injury [31,32,33,34,35,36]. As seen in the vascular injury model, we showed that administration of exogenous NRG-1 was neuroprotective and prevented inflammatory responses caused by ischemia [32, 37].…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, ERBB4 and CYBA were in the network diagram of 1-month and 2-week post-SCI group vs. control group, and all samples, respectively. Lindholm et al ( 33 ) demonstrated that in the vicinity of the lesion, a number of scattered cells expressed ErbB mRNA following SCI. Neuregulin1/ErbB signaling may be involved in the development of SCI ( 34 ).…”
Section: Discussionmentioning
confidence: 99%